2021
DOI: 10.3390/nu13061982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cholesterol-Lowering Mechanism of Enterococcus faecium Strain 132 and Lactobacillus paracasei Strain 201 in Hypercholesterolemia Rats

Abstract: Hypercholesterolemia can cause many diseases, but it can effectively regulated by Lactobacillus. This study aimed to evaluate the cholesterol-lowering mechanism of Enterococcus faecium strain 132 and Lactobacillusparacasei strain 201. These results showed that both the strains decreased serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglycerides (TG), liver TC and TG and increased fecal TC, TG and total bile acid (TBA) levels. Additionally, both strains also reduced glutamic-pyruvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Accumulation of lipids in the liver is the main cause of non-alcoholic fatty liver disease (NAFLD), which is a common complication of obesity (Skrypnik et al, 2018 ). Furthermore, multiple studies have shown that obesity is directly connected with body-liver weight, liver TC and liver TG, and serum lipid profiles in high-fat diet-induced obese rats (Skrypnik et al, 2018 ; Wang et al, 2021 ; Yang et al, 2021 ). In our experiments, it was evident that the high-fat diet-fed rats (HCD rats) showed an increased TC and TG levels from both the serum and liver tissue homogenate, which further triggered the lipid accumulation and lipotoxicity in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of lipids in the liver is the main cause of non-alcoholic fatty liver disease (NAFLD), which is a common complication of obesity (Skrypnik et al, 2018 ). Furthermore, multiple studies have shown that obesity is directly connected with body-liver weight, liver TC and liver TG, and serum lipid profiles in high-fat diet-induced obese rats (Skrypnik et al, 2018 ; Wang et al, 2021 ; Yang et al, 2021 ). In our experiments, it was evident that the high-fat diet-fed rats (HCD rats) showed an increased TC and TG levels from both the serum and liver tissue homogenate, which further triggered the lipid accumulation and lipotoxicity in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous strains of Bifidobacterium and Lactobacillus species have been reported to alleviate cholesterol both in vivo and in vitro , very limited reports are available for the hypocholesterolemic effect of the Enterococcus strains (Tomaro-Duchesneau et al, 2014 ; Shehata et al, 2016 ; Hyrslova et al, 2021 ; Marras et al, 2021 ; Yang et al, 2021 ; Kouhi et al, 2022 ). Thus, this study has aimed to determine the beneficial effects of probiotic Enterococcus durans HS03 (BSH-negative) and Enterococcus lactis YY1 (BSH-positive) on lipid metabolism in Sprague–Dawley rats fed with a high-cholesterol diet.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of rats fed a high-fat diet, 24-h supplementation of Enterococcus hirae (2 mg/10 10 CFU) decreased total cholesterol and TG levels and alleviated insulin resistance ( 41 ). A recent study with hypercholesterolemic rats, administration of specific strains of Enterococcus faecium decreased total cholesterol, LDL-C, and TG levels by regulating the genes involved in lipid metabolism, such as CYP8B1 , CYP7A1 , SREBP-1 , SCD1 , and LDL-R ( 42 ). Thus, the benefit of LPK on lipid profiles might be driven by favorable alterations in the distribution of gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney was rinsed with PBS and fixed in 10% buffered formalin for 24 h. The kidney tissue was then dehydrated with an alcohol gradient, embedded in paraffin and sliced. Finally, the tissue was dewaxed using xylene and stained using hematoxylin-eosin (HE) [ 20 ]. We chose the kidney as the pathological section to know the protective effect of Lactiplantibacillus plantarum fermented milk on kidney damage caused by hypertension, because hypertension often causes some complications, especially the kidney [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%